This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I Like It!!!
Elegant!!!
such a nice solution!thanks a lot!
Ingenious approach!
it's great to me!!!
So 2a gets cancelled out by a ?
Log in to reply
No he just transform it from a^2+2ab+b^2 to (a+b)^2 a=9999 and b=1
perfect answer, I have a question about my approach that was incorrect: say a = 9999, like you said given expression cannot become? \sqrt{a^2 + (a+10000)}, why is this wrong, I am not seeing it.
Log in to reply
It's true also but you have to transform it to the form a^2+2ab+b^2 to be able to simplify it because that expression equal (a+b)^2
The simplest way!!!!
Wow, I didn't even look at it that way...
But 2×9999=19998!! And given is 1999
Log in to reply
That's right, "2a" is 19998, and since the number shown is 19999, it can be re-written as 2a.... + 1 Just a different way to write it.
The idea is interesting.
Nice solution
Complicated question. Simple solution. Wow.
Ohh man thats what I thinking
My God!!!!
So what happened to 2a?
Log in to reply
You can factor a 2 + 2 a + 1 by grouping to get
= ( a 2 + a ) + ( a + 1 )
= a ( a + 1 ) + 1 ( a + 1 )
= ( a + 1 ) ( a + 1 )
= ( a + 1 ) 2
Cool I wonder how could I miss this :p
Why would you squire root (a+1)^2
Clever. Thanks for explanation!
darn whne i see all these people asking where did 2a go i facepalm
a+1 * a+1 = a(a+1)+1(a+1)=a^2+2a+1 there's your 2a
Well Answered
but the equation is a x a + a^2
9 9 9 9 × 9 9 9 9 + 1 9 9 9 9
= 9 9 9 9 × 9 9 9 9 + 1 0 0 0 0 + 9 9 9 9
= 9 9 9 9 × ( 9 9 9 9 + 1 ) + 1 0 0 0 0
= 9 9 9 9 × 1 0 0 0 0 + 1 0 0 0 0
= 1 0 0 0 0 × ( 9 9 9 9 + 1 )
=10000
That's what the solution I used to solve. Nice
This is the best solution.
I like your answer
Good solution
Whats the name of the law?
This is the best solution
Where did the one come from? I'm a little confused.
Log in to reply
Breaking out 10000 from 9999 x 10000 + 10000 Since 10000 / 10000 = 1 we are left with 10000 x ( 9999 + 1)
How are the second and third line the equal? You removed an entire value (9999) and you changed the equation by changing the amount being multipied..
Log in to reply
Now tell me, does 9999 x 9999 + 9999 = 9999 x (9999 + 1) or 9999 x 10000
Easy explanation and with respect to the question
Quadratic equation
Easy to understand
X = 9 9 9 9 × 9 9 9 9 + 1 9 9 9 9 = 9 9 9 9 × 9 9 9 9 + 1 9 9 9 8 + 1 = 9 9 9 9 2 + 2 ( 9 9 9 9 ) + 1 = x 2 + 2 x + 1 = ( x + 1 ) 2 = x + 1 = 9 9 9 9 + 1 = 1 0 0 0 0 Let x = 9 9 9 9 Put back x = 9 9 9 9
it's great !
Best step by step
Rock it bro
For your second statement you had 19998+1. Why is that?
Log in to reply
1 9 9 9 9 = 1 9 9 9 8 + 1 = 2 ( 9 9 9 9 ) + 1 = 2 x + 1
@ivan that's because 19999=19998+1. gasp
nice solution
9 x 9 = ends in 1, 1 + 9 ends in 0, 10000 is the only choice that ends in 0
Good mathamatical logic..
That's exactly how I did it!!!
Pls tellme also b/c i wants know everythingh about math i am crazy about math and you brliant in maths
That's what I did!
Haha I did it the same way XD
9 9 9 9 = 1 0 4 − 1
1 9 9 9 9 = 2 0 0 0 0 − 1 = 2 × 1 0 4 − 1
( 1 0 4 − 1 ) 2 + 2 × 1 0 4 − 1
( 1 0 4 ) 2 − 2 × 1 0 4 + 1 + 2 × 1 0 4 − 1
( 1 0 4 ) 2 = 1 0 4 = 1 0 0 0 0
Why dose using this method help? And how does it compare from the other ones in this chat?
because 9x9 equals 81, and the ending number of the answet is 1. Also the ending number of 19999 is 9. 1+9 equals to 10, so only 10000 is thr answer.
A fast solution: Notice that 9999 × 9999 first digit is 1 and 19999 first digit is 9 so their sum must be a power of ten.. then 10000 must be the solution.
xyz9*xyz9=abcde1
abcde1+efgh9 = rtyub0
√rtyub0 should end with 0
The only answer that ends with 0 in choices is 10000
9 9 9 9 × 9 9 9 9 + 1 9 9 9 9 = 9 9 9 9 2 + 1 9 9 9 8 + 1 = 9 9 9 9 2 + 2 × 9 9 9 9 × 1 + 1 2 = ( 9 9 9 9 + 1 ) 2 = 1 0 0 0 0 2 = 1 0 0 0 0
We must find the square root of: 9 9 9 9 ∗ 9 9 9 9 + 1 9 9 9 9 = ( 1 0 4 − 1 ) 2 + 1 0 4 + 1 0 4 − 1 = ( 1 0 4 − 1 ) 2 + 2 ∗ 1 0 4 − 1 = A.
Let x = 1 0 4 . Then: A = ( x − 1 ) 2 + 2 x − 1 = x 2 − 2 x + 1 + 2 x − 1 = x 2 = ( 1 0 4 ) 2 . Then the root is clearly 1 0 4 .
9x9 is 81. 81+9 = 90 which ends in a zero. The whole number of any square root of a number that ends in a zero must also end in a zero and there was only 1 answer that ended in a zero. Lateral thinking.
9x9 is 81.
81+9 = 90 which ends in a zero.
The whole number of any square root of a number that ends in a zero must also end in a zero and there was only 1 answer that ended in a zero
9*9=81 so the digit of the unity of the product is 1 and those of the other nomber is 9 do with the sum we will have a number like that under the square "xxxxxx0" because the last digit is a 0 the last digit of the result is a 0 too so only 10000 can be correct
9×9=81 take the "1" digit. 1+9=10 so it must be 10000, since the other answers end in other ways :')
Multiply 9 by 9, the result will give 1 (least significant bit). And when adding 9 receive 0 (least significant bit) and there is only one answer fits.
9 9 9 9 × 9 9 9 9 + 1 9 9 9 9 = = = = = = 9 9 9 9 2 + 9 9 9 9 + 1 0 0 0 0 9 9 9 9 2 + 9 9 9 9 + 9 9 9 9 + 1 9 9 9 9 2 + 2 ( 9 9 9 9 ) ( 1 ) + 1 2 ( 9 9 9 9 + 1 ) 2 9 9 9 9 + 1 1 0 0 0 0
9 9 9 9 × 9 9 9 9 + 1 9 9 9 9 = 9 9 9 9 2 + 1 0 0 0 0 + 9 9 9 9 = 9 9 9 9 ( 9 9 9 9 + 1 ) + 1 0 0 0 0 = 9 9 9 9 ( 9 9 9 9 + 1 ) + ( 9 9 9 9 + 1 ) = ( 9 9 9 9 + 1 ) ( 9 9 9 9 + 1 ) = ( 9 9 9 9 + 1 ) 2 = 9 9 9 9 + 1 = 1 0 0 0 0
LaTeX\(\sqrt{(10000-1)(10000-1)+ (2000 -1))} = ( ( 1 0 0 0 0 2 − 2 0 0 0 0 + 1 ) + 2 0 0 0 − 1 ) = ( 1 0 0 0 0 2 ) (LaTeX(10000)
x =(10000-1)(10000-1) + 19999 =10000^2 +1 -2×10000 +19999 =10000^2 -20000 +20000 =10000^2 so x^1/2 = 10000
General solution: sqrt [ (10^n-1)^2 + 2 10^n - 1] = sqrt [ 10^(2n) + 1 - 2 10^n + 2*10^n - 1] = sqrt [ 10^(2n) ] = 10^n
For this problem, set n = 4 to get the correct answer, i.e. 10000.
you can figure any square, and it's square root, if you know what the previous square is. take the previous square, add its square root and the next highest number.
9999^2=99980001
10000^2=100000000
100000000-99980001=19999
19999-9999=10000
not sure anyone will follow that.
9x9 + 19 = 10 So let's bring back the other decimals. = 100000 Sqroute = 10000
Not the best way, but how I did it: You know that 9999 x 9999 ends with the digit 1 (because 9 x 9 = 81). Adding a number ending with the digit 1 will give a number that ends with the digit 0. The only choice that will have a square that ends with the digit 0 is 10000.
9999 X 9999 = 10000 ×9999 - 9999 So now √10000 ×9999 -9999 + 19999 =√ 10000×9999 +10000 = √10000( 9999 + 1 ) = √ 10000 ( 10000) = 10000
Why not (9999)(9999) then + 19999 = 100,000,000 and take the square of that?
(99.99×100×99.99×100+1.9999×10000)^.5. =100×(99.99^2+1.9999)^.5=100×((100-.01)^2+1.9999)^.5=100×(10000+.0001-2+1.9999)^.5 =100×100=10000####
Let x= 10000
sqrt( (x-1)^2 +2x-1) sqrt(x^2-2x+1 +2x-1) sqrt(x^2) x
Therefore, the answer is 10000
9999 x 9999+ 9999 +10000 one extra lot of 9999 10000 x 9999 + 10000 Factorise 10000(9999 + 1) = 10000 x 10000 Therefore sqrt(10000 x 10000) = 10000
Problem Loading...
Note Loading...
Set Loading...
Let a = 9 9 9 9
So , the given expression becomes -
a 2 + 2 a + 1
= ( a + 1 ) 2
= a + 1
= 9 9 9 9 + 1
= 1 0 0 0 0